2012
DOI: 10.1155/2012/175019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Impairment and Depression among a Population Aged over 60 Years in the Metropolitan Area of Guadalajara, Mexico

Abstract: Background. Cognitive impairment is an important clinical issue among elderly patients with depression and has a more complex etiology because of the variable rate of neurodegenerative changes associated with depression. The aim of the present work was to examine the prevalence of cognitive impairment and depression in a representative sample of adults aged ≥60 years. Methods. The presented work was a cross-sectional study on the prevalence of cognitive impairment and depression. Door-to-door interview techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
17
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
9
17
1
8
Order By: Relevance
“…These data coincide with the studies in Jalisco and México where the prevalence of cognitive impairment and depression was reported previously [29, 30], suggesting that prevalence of both conditions has not changed in the last few years.…”
Section: Discussionsupporting
confidence: 91%
“…These data coincide with the studies in Jalisco and México where the prevalence of cognitive impairment and depression was reported previously [29, 30], suggesting that prevalence of both conditions has not changed in the last few years.…”
Section: Discussionsupporting
confidence: 91%
“…As regards cognitive impairment associations in this study, significant association was noticed only with age, a result that is similar to that obtained by Ortiz et al [16]. Also, Chen et al [24] found that cognitive changes in hospitalized elderly were predicted by age.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of depressive symptoms among 200 elderly medical inpatients was 72% according to GDS. Prevalence rates of depression showed wide variability in studies that assessed it among elderly [16]. These differences may be due to the differences between communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, recientes investigaciones describen la importancia de la sintomatología menopaúsica sobre los demás factores (16,19), teorizándose que la presencia de alteraciones en los principales dominios sintomáticos puede producir un efecto en cascada que aumente el riesgo para la aparición del TDM (20). Considerando no sólo la importancia de estos factores en la salud mental de las mujeres, sino además las proyecciones epidemiológicas que predicen que la tasa de mujeres durante la menopausia aumentará en los siguientes años hasta representar más del 30% de las mujeres mexicanas (21,22), crea la necesidad de estudiar esta problemática antes de convertirse en un grave problema de salud pública. Por lo tanto, se pretende determinar el riesgo de presentar TDM al haber alteraciones en la sintomatología menopaúsica u otras características sociodemográficas y clínicas de las mujeres.…”
Section: Introductionunclassified